Rovibrational Energy Levels and Photoabsorption Spectra of the Isotopically Substituted N2O: A Theoretical Study - Daud, Mohammad Noh; Balint-Kurti, Gabriel G. (Malaysian Journal of Science, 2009)
The rovibrational spectra of the ground electronic state potential energy surface, X1 A', for the 14N15N16O, 15N14N16O, 15N15N16O, 14N14N17O and 14N14N18O isotopomers have been calculated variationally by fixing the total angular momentum at J= 0 with parity state either even or odd, and J= 1 with odd parity state. Theoretical results show good agreement with the experimental observations for the three lowest vibrational states namely (0, 00, 0), (0, 11, 0) and (0, 20, 0) with maximum discrepancy of 20.95 cm-1. Using the ground state wavefunctions of the five heavy isotopomers and the corresponding transition dipole moments connecting to the three lowest singlet excited state potential energy surfaces (21 A', 11 A" and 21 A" ), the resulting theoretical absorption spectra show in excellent agreement with the experimental spectra.